ROLE OF MICROFINANCE INSTITUTIONS IN PROMOTING FINANCIAL INCLUSION - Renjith, M Josephine; Sindoora S (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Microfinance institutions (MFIs) have emerged as crucial agents in fostering financial inclusion, particularly in developing economies. This paper explores the role of MFIs in promoting financial inclusion in Kerala, India. Through a structured survey using a 5-point Likert scale-based questionnaire administered to a randomly selected sample of 300 beneficiaries, the study examines the extent of financial inclusion facilitated by MFIs. Data analysis was carried out using EDUSTAT software, employing descriptive statistics and hypothesis testing. Results indicate that MFIs significantly contribute to enhancing access to financial services, particularly among marginalized communities. The findings underline the need for strengthening the microfinance framework to ensure sustainable inclusion. This paper highlights the importance of strategic policy initiatives and recommends avenues for future development in the sector.